The music of Nobuo Uematsu in the Final fantasy series - Anatone, Richard (Studies in game sound and music., 2022)
This is the first book-length study of the music of Nobuo Uematsu, and focuses on his Final Fantasy soundtracks, exploring the dynamic relationship between the music and the stories behind the beloved video game series. Contributors are music and game scholars, based in the USA and UK. Foreword by William Gibbons. 95 b/w illus.